(untitled) (Revista científica Olimpia, 2022)
This study is part of a proposal for general and special exercises for muscle strengthening of disabled athletes in the category F-56 (Spinal cord injuries) in the discus throw in order to increase sports results. In this sense, the research methods of the theoretical and empirical level are used; as well as mathematical statistical methods, to investigate a population of 6 male athletes with discus throw physical motor disabilities from 2017-2019. The proposal of exercises for the increase of the muscular force of the athlete, objects of study, as a means of physical preparation, accessed the increase of the coefficients of the force levels, is based on a methodological base that will allow the coach to plan the work correctly. of the different types of preparation, counting on the methods, contents and means for its development.